Pengaruh Tegangan Dan Massa Flywheel Serta Interaksinya Terhadap Energi Kinetik Pada Flywheel Cakram - Ahmad Nur Wahyudi; Wirawan Wirawan (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effect of electrical voltage and flywheel mass on the kinetic energy produced by the starter motor, as well as to evaluate the geometric shape of the flywheel. The kinetic energy in the flywheel is influenced by the moment of inertia and angular velocity produced by the starter motor. The study was conducted exprerimentally using a quatitative approach, with variations in voltage (11V-14V) and flywheel mass (0.9-1.2 kg), and analyzed using a Two-Way ANOVA Faktorial test. The results show that both voltage and flywheel mass significantly affect kinetic energy, with increased voltage linearly increasing RPM and energy, and a larger mass increasing the moment of inertia. The interaction between the two is synergistic, with the combination of 1.2 kg and 14V voltage yielding the highest energy (4.0 Joules), and an R-squared value of 97.65 % indicating the model is highly accurate. These findings support the development of efficient mechanical energi storage system and optimal flywheel design.